2022
DOI: 10.3390/polym14153116
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Prunus domestica Based Natural Gum on Physicochemical Properties of Polyaniline for Corrosion Inhibition of Mild and Stainless Steel

Abstract: The lack of an eco-friendly approach towards application of polyaniline as a coating material has been one of the most challenging tasks. Herein, the synthesis of green Prunus domestica gum grafted polyaniline (PDG-g-PANI) composite is reported by a cost-effective emulsion polymerization for application as an efficient anti-corrosion material for mild steel (MS) and stainless steel (SS) in a strong corroding environment. The composite formation was confirmed by Ultraviolet Visible (UV-Visible) and Fourier Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It was found that the composite is soluble in alcohols, especially methanol and ethanol/propanol, which is due to the presence of polar components such as –NH and –OH, which are responsible for the solubility in polar solvents. Such solubility can be attributed to the formation of hydrogen bonds between composites and alcohols [ 20 ]. The same phenomenon occurred when the composite approached NMP and THF, albeit these solvents differ significantly from alcohols.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the composite is soluble in alcohols, especially methanol and ethanol/propanol, which is due to the presence of polar components such as –NH and –OH, which are responsible for the solubility in polar solvents. Such solubility can be attributed to the formation of hydrogen bonds between composites and alcohols [ 20 ]. The same phenomenon occurred when the composite approached NMP and THF, albeit these solvents differ significantly from alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…The region at 556 nm is attributed to the π-polaron transition, while the peak at 407 nm is attributed to the polaron π*-transition of the quinoid ring. Peaks at 301 nm and 261 nm are attributed to the π-π*-transition of the benzoid ring and the arabinogalactose component of PDG, respectively [ 20 ]. The UV/Vis spectra of PDG-g-PANI/Al 2 O 3 gave three sharp peaks at 251 nm, 290 nm, and 403 nm, while there was one broad peak at 573 nm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations